2007
DOI: 10.1186/1479-5876-5-61
|View full text |Cite
|
Sign up to set email alerts
|

A function blocking anti-mouse integrin α5β1 antibody inhibits angiogenesis and impedes tumor growth in vivo

Abstract: BackgroundIntegrins are important adhesion molecules that regulate tumor and endothelial cell survival, proliferation and migration. The integrin α5β1 has been shown to play a critical role during angiogenesis. An inhibitor of this integrin, volociximab (M200), inhibits endothelial cell growth and movement in vitro, independent of the growth factor milieu, and inhibits tumor growth in vivo in the rabbit VX2 carcinoma model. Although volociximab has already been tested in open label, pilot phase II clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 29 publications
3
40
0
1
Order By: Relevance
“…Indeed, genetic deletion of FN leads to embryonic death due to the indispensible role of FN in developmental branching morphogenesis (42)(43)(44). Prior studies in endothelial cells have revealed that the FN-integrin complex is requisite for FN-induced chemotaxis and angiogenesis (45)(46)(47)(48), with both ␣v␤3 and ␣5␤1 implicated in this process (35,36,39). Another study on IGF-I receptor also found FN may transactivate this receptor via ␤3 integrin to protect cells from apoptosis (49).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, genetic deletion of FN leads to embryonic death due to the indispensible role of FN in developmental branching morphogenesis (42)(43)(44). Prior studies in endothelial cells have revealed that the FN-integrin complex is requisite for FN-induced chemotaxis and angiogenesis (45)(46)(47)(48), with both ␣v␤3 and ␣5␤1 implicated in this process (35,36,39). Another study on IGF-I receptor also found FN may transactivate this receptor via ␤3 integrin to protect cells from apoptosis (49).…”
Section: Discussionmentioning
confidence: 99%
“…Volociximab is found to inhibit angiogenesis and hinder tumor growth. 102,103 Clinical efficacy and tolerance of volociximab was found satisfactory in phase I trial. 104 This observation led this to phase II trial for solid tumor.…”
Section: -100mentioning
confidence: 95%
“…Genetic deletion of 5 integrin in mice leads to embryonic death owing to extensive vascular and mesodermal defects (Francis et al, 2002). Consistently, 5 integrin antagonists inhibit angiogenesis induced by tumors or growth factors in adult mice (Bhaskar et al, 2007;Kim et al, 2000). Furthermore, 51 integrin was shown to influence endothelial cell survival in vivo (Kim et al, 2002) and induces endothelial cell proliferation (Mettouchi et al, 2001).…”
Section: Introductionmentioning
confidence: 91%